2022
DOI: 10.1021/jacs.2c12151
|View full text |Cite
|
Sign up to set email alerts
|

Borenium-Ion-Catalyzed C–H Borylation of Arenes

Abstract: Non-metal-catalyzed C−H borylation of arenes represents a sustainable and environment-friendly approach for the functionalization of arenes. Despite its promise as an alternative to traditional transition-metal systems, its substrate scope is generally limited to electron-rich arenes, thus hindering its application in organic synthesis. Herein, we report the development of a borenium-ion catalyst which can borylate unactivated arenes under ambient conditions with 4-chlorocatecholborane (HBcat Cl ) as borylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 81 publications
1
20
0
Order By: Relevance
“…and pentamethylbenzene were examined. These substrates also showed good reactivity and the reactions did not give any undesirable side products (20)(21)(22)(23), likely due to the low reaction temperature insufficient to promote alkyl shifts. It should be noted that direct C-H borylation of these sterically hindered multi-alkylbenzenes is challenging and hardly be obtained at room temperature by other methods 21 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…and pentamethylbenzene were examined. These substrates also showed good reactivity and the reactions did not give any undesirable side products (20)(21)(22)(23), likely due to the low reaction temperature insufficient to promote alkyl shifts. It should be noted that direct C-H borylation of these sterically hindered multi-alkylbenzenes is challenging and hardly be obtained at room temperature by other methods 21 .…”
Section: Resultsmentioning
confidence: 97%
“…However, the steric control can also limit the scope of alkylbenzenes because the catalyst cannot access sterically hindered C–H bonds, notably those ortho to alkyl groups. Consequently, transition-metal catalyzed borylation of sterically hindered arenes such as mesitylene where all aromatic C–H bonds are ortho to alkyls has been limited 21 , 22 . An exceptional example was reported by Chatani et al utilizing an NHC-ligated platinum catalyst, [(ICy)Pt(dvtms)] (ICy = 1,3-dicyclohexylimidazol-2-ylidene, dvtms = divinyltetramethyldisiloxane) where sterically encumbered alkylbenzenes such as mesitylene could be borylated to give corresponding aryl boronic esters 21 .…”
Section: Introductionmentioning
confidence: 99%
“…A highly electrophilic [(NacNac)­Zn] + derivative is able to bind catecholborane (CatBH) and activate it to a greater extent (based on the relative CatB-based LUMO energies) than when using [(NHC)­ZnR] + electrophiles. This leads to an expanded substrate scope for catalytic C–H borylation, with this FLP-catalyzed borylation being the first such process able to borylate weakly activated heteroarenes such as 2-bromothiophene and benzothiophene . The robust and well-defined nature of the [(NacNac)­Zn­(DMT)] + precatalyst enabled detailed computational analysis which indicated that an endergonic, but kinetically accessible, displacement of DMT by CatBH at zinc is essential to get on cycle.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to an expanded substrate scope for catalytic C–H borylation, with this FLP-catalyzed borylation being the first such process able to borylate weakly activated heteroarenes such as 2-bromothiophene and benzothiophene. 30 The robust and well-defined nature of the [(NacNac)Zn(DMT)] + precatalyst enabled detailed computational analysis which indicated that an endergonic, but kinetically accessible, displacement of DMT by CatBH at zinc is essential to get on cycle. This formed an adduct containing a short Zn···O (CatBH) interaction and a strongly activated CatBH moiety that can be viewed as a borenium cation equivalent.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, a breakthrough example was reported by Wang and co‐workers, who achieved a borenium‐ion‐catalyzed C−H borylation of unactivated arenes and phenols with 4‐chlorocatecholborane (HBcat Cl ) as the borylating agent under ambient conditions (Scheme 5). [22] This metal‐free catalytic system is suitable for the borylation of C−H bonds in sterically encumbered positions and para position of phenols, which has been a challenging task for transition‐metal systems. Mechanistically, a synergistic activation of the H−Bcat Cl bond by the arene substrate and the (NHC)‐stabilized o ‐carboranyl‐substituted borenium‐ion catalyst generates a Wheland intermediate and a neutral hydroborane species.…”
Section: Aromatic C−h Borylationmentioning
confidence: 99%